AB0312 Detection of Cardiovascular Risk Factors in Outpatient Rheumatology Service. (10th June 2014) - Grados, D.; Lόpez-Vives, L.; Rotés, I.; Erra, A.
Abstract : Background: The chronic inflammatory process in patients with rheumatoid arthritis (RA) acts as an independent cardiovascular (CV) risk factor. Hence they have an higher risk of developing cardiovascular disease compared to healthy people of the same age and sex. This increased risk is being evaluated in other chronic inflammatory rheumatic diseases. Besides the control of rheumatic disease, it is necessary to evaluate other factors of CV risk as lipid profile, blood pressure (BP) and blood glucose. Objectives: The aim of this study was to determine CV risk factors in a series of patients with chronic inflammatory rheumatic diseases follow up in Rheumatology Service. Methods: We conducted a prospective observational study during 6 months (April to October 2013) in a population of patients older than forty years with chronic inflammatory rheumatic diseases. We collected the medical history of hypertension, diabetes, dyslipidemia, ischemic heart disease (IHD) and smoking habit. BP, blood glucose and lipid profile (total cholesterol, low-density lipoprotein –LDL-, high-density lipoprotein –HDL- and triglycerides) were measured. CV risk has been analyzed by the REGICOR and modified SCORE function by RA EULAR consensus. Results: A total of 125 patients were enrolled, 82 women (66%) and 43 men (34%) with a mean age of 61 years (40-89 years). We included 79 patients with RA (63%), 23 with psoriatic arthritis (18%), 15 with ankylosing spondylitis (12%), 5 with palindromic rheumatism (4%) and 3 with arthritis associated with inflammatory bowel disease (3%). At the time of registration, 37 patients were active smokers (30%). In all patients were determined: BP, with a mean of 138 mmHg (90 - 190mmHg) systolic BP, serum lipid profile determination, obtaining mean values of total cholesterol 1.97g/L, HDL 0.64 g/L, LDL 1.09 g/L and triglyceride 1.17 g/L. At baseline, 42 patients had diagnosed and had treated with hypertension (34%), 14 patients with diabetes mellitus (11%) and 29 patients with dyslipidemia (23%). Six patients had a history of IHD. In outpatient it found systolic BP greater than 140 mmHg in 60 patients, 32 of whom were undiagnosed hypertension. High cholesterol levels (greater than 2g/L) were found in 59 patients, 47 of which were previously undiagnosed dyslipidemia. No patient was diagnosed of diabetes mellitas. The mean SCORE and REGICOR was 3.61 (0-19) and 3.99 (1-12) respectively, both values are considered low cardiovascular risk. In 11 patients (9%) CV risk was high (above 10), 2 patients were active smokers, 3 patients were not known hypertension and 5 patients were detected an unknown dyslipidemia. Conclusions: Unknown hypertension was detected in 26% of patients and dyslipidemia in 38%. High CV risk was found in 9% of patients with chronic inflammatory rheumatic disease, and in some cases modifiable CV risk factors undiagnosed. Patients with chronic inflammatory rheumatic diseases necessitates careful monitoring of all factors of CV risk. Outpatient Rheumatology is a good place screening of these risk factors and may be useful for the prevention of future CV events. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4090